The Impact of Social Media on Generation Z Education in Indonesia - Umar Fathurrohman; Sovian Aritonang; Aris Sarjito; Mhd Halkis; Robby M. Taufik (South Sulawesi Education Development (SSED), 2024)
This study explores the impact of social media on the education of Generation Z in Indonesia, focusing on learning styles, social interactions, and the challenges and opportunities they face. Using a mixed methods approach, the study combines quantitative data from surveys and qualitative data from in-depth interviews to gain a comprehensive understanding. Key findings suggest that social media, such as YouTube and Instagram, have become essential tools in supporting students’ access to information and collaboration. These platforms facilitate more interactive and engaging learning, allowing students to grasp complex concepts more easily. However, challenges such as gaps in technology access and potential distractions remain. The study recommends the development of new learning strategies that effectively integrate social media, as well as educational policies that support constructive social media use. Further research is recommended to investigate digital literacy, the long-term impacts of social media use, and policies that can address the digital divide, in order to maximize the benefits of social media in education.